O perifíton em riachos experimentais como ferramenta de avaliação dos efeitos do rejeito de mineração de ferro no Rio Doce, ES. - Reis, Luciane Ayres Castro (2023)
This thesis investigates the impact of iron mining tailings from the Fundão dam collapse in Mariana-MG on the periphyton, which is a group of primary producers in aquatic ecosystems. Despite the classification of tailings as inert and nonhazardous, the lack of biological studies immediately after the dam collapse has hindered the understanding of their interaction with affected ecosystem processes, as well as the long-term effects of the disaster. To study the effects of tailings collected from inside the dam, periphyton was selected as a bioindicator due to its high biodiversity and short development time, which is typically on the scale of days to weeks. It also has a key position at the base of the food chain and in the metabolism of rivers. The experimental technique of the stream microcosm offers the advantage of establishing causal relationships while maintaining the ecological relevance of the results. These advantages are further enhanced by the use of periphyton as a bioindicator due to its relevant ecological position at community and micro-ecosystem levels, as well as the small space requirement for its development. The thesis is divided into six chapters. Chapter two is a systematic review of 73 case studies on periphyton in experimental streams, aimed at analyzing the current state-of-the-art on this subject and proposing a methodological roadmap for experimental development. Chapter three of the thesis details the creation of an experimental model, based on a specific roadmap, which was then used to evaluate the impact of iron mining tailings from the Fundão dam in Minas Gerais. In chapter four, the effects of these tailings on the structure and functioning of the periphyton were investigated. The results showed a trend towards recovery in primary production and physicochemical indicators. In chapter five, the focus shifted to the periphytic diatom community of live samples, which were examined using physiological indicators. The study revealed that larger, stalked and mobile algae survived, while adherent and smaller algae experienced mortality. Chapter five also explored the ecological stoichiometry of nutrients and algal classes, and identified a progressive divergence of reference values for these indicators. Throughout the study period, cyanobacteria dominated the streams receiving the tailings, while diatoms dominated the treatments. Despite the increasing availability of dissolved silica, the algal classes exhibited long-term structural changes that could have detrimental effects on the trophic chain, including humans. The thesis concludes that periphyton in experimental streams is a sensitive tool for investigating environmental stressors, such as the effects of iron mining tailings.